Math fables too : making science count - Tang, Greg.; Morley, Taia (New York : Scholastic Press, 2007)
Fables about ocean, jungle, desert, and lake animals teach about number groupings and counting, laying the groundwork for addition.
Kirkus Review
School Library Journal
3.0
K-3
K-3
Keywords: Counting -- Juvenile literature; Science -- Juvenile literature; Counting; Science; Counting; Science